Non-compaction of the ventricular myocardium - Livio Dei Cas; Marco Metra; Savina Nodari; Enrico Vizzardi (Heart International, 2006)
Non-compaction of the left ventricle (LVNC) is a disorder of endomyocardial morphogenesis that results in multiple trabeculations in the left ventricular (LV) myocardium. This rare disorder is characterized by an excessively prominent trabecular meshwork and deep intratrabecular recesses. This idiopathic cardiomyopathy is characterized by an altered structure of the myocardial wall as a result of intrauterine arrest of compaction of the myocardial fibers in the absence of any coexisting congenital lesion. It can be associated with neuromuscular disorders and can co-exist with other cardiac malformations, and it is accompanied by depressed ventricular function, systemic embolism and ventricular arrhythmia. Echocardiography is the method of choice for diagnosing LVNC, but the correct diagnosis is often missed or delayed due to a lack of knowledge concerning this uncommon disease and its similarity to other diseases of the myocardium and endocardium. There is a two-layered structure of the myocardial wall consisting of a thin compacted epicardial layer and a thick non-compacted endocardial layer with prominent trabeculations and deep recesses. (Heart International 2006; 3-4: 178-83)